Habitat modeling of little tuna (Euthynnus affinis) in Makassar Strait (Indonesia) using MaxEnt - ANDI RISDA FITRIANTI ABUDARDA; MUKTI ZAINUDDIN; RACHMAT HIDAYAT; SITI KHADIJAH SRIOKTOVIANA (Society for Indonesian Biodiversity, 2026)
Abstract. Abudarda ARF, Zainuddin M, Hidayat R, Srioktoviana SK. 2026. Habitat modeling of little tuna (Euthynnus affinis) in Makassar Strait (Indonesia) using MaxEnt. Biodiversitas 27 (1): d270142. https://doi.org/10.13057/biodiv/d270142. Euthynnus affinis, commonly known as little tuna, is an ecologically and economically important pelagic species that supports artisanal and commercial fisheries across the Indo-Pacific region. The Makassar Strait, a major pathway of the Indonesian Throughflow, exhibits pronounced seasonal and interannual variability in oceanographic conditions, which strongly influences the spatial and temporal distribution of pelagic fishes. This study presents the first application of the Maximum Entropy (MaxEnt) modeling framework to predict habitat suitability for E. affinis in the Makassar Strait. Presence-only occurrence records were related to key environmental variables derived from satellite observations, including sea surface temperature (SST), sea surface chlorophyll concentration (SSC), and sea surface salinity (SSS). SST and SSC data were obtained from the MODIS Aqua sensor (NASA Ocean Color) at a spatial resolution of 4 km, while SSS data were sourced from the Copernicus Marine Environment Monitoring Service. All environmental variables were compiled at a monthly temporal resolution from January 2019 to December 2023. The MaxEnt models showed strong predictive performance, with area under the curve values ranging from 0.78 in July to 0.92 in April, indicating good to excellent model accuracy. SST emerged as the most influential predictor, contributing 57.4 percent to model gain, followed by SSC and SSS. Habitat suitability was highest in the central and southern sectors of the strait, particularly during periods characterized by moderate SST and elevated SSC. Euthynnus affinis showed a preference for SST of approximately 29.31°C, SSC of 0.22 mg m⁻³, and SSS of 33.7 psu. Optimal habitats were largely concentrated in the southern Makassar Strait, especially around 4 to 5°S. These results demonstrate a clear association between regional oceanographic dynamics and the distribution of E. affinis. The findings provide essential baseline information for ecosystem-based fisheries management and support adaptive strategies for small-scale fisheries. Integrating these spatio-temporal habitat patterns into regional fisheries planning may improve resilience to environmental variability and help sustain tuna fisheries in the Makassar Strait.